(untitled) (Revista Contexto & Saúde, 2026)
Objective: To describe the eating habits and the consistencies of the food consumed, relating them to facial anthropometry and masticatory characteristics of the individuals diagnosed with temporomandibular disorder compared to a control group. Method: The study included 40 individuals who answered an online questionnaire. After applying the inclusion and exclusion criteria, the individuals were called for a clinical evaluation. For the dental evaluation we used the DC/TMD protocol, while in the speech evaluation we used parts of the MBGR protocol. Data on facial anthropometry, mandibular movement measurements, and masticatory function were collected. The sample was divided, for purpose of assessment, into a control group and a group with temporomandibular disorder. Results: Participants in the group with temporomandibular disorder classified some foods as harder to chew than those in the control group (p=0.043). The group with temporomandibular disorder presented smaller mouth opening, reduced mandibular laterality, and greater vertical dimension of occlusion. Both groups predominantly used alternating bilateral chewing (control group: 80% and temporomandibular disorder group: 75%), but only the temporomandibular disorder group presented chronic unilateral chewing (20%), besides showing more alterations in their orofacial motor skills. Conclusion: Temporomandibular disorder can influence certain eating habits. The preference for softer food consistencies is possibly related to an attempt to minimize chewing discomfort, which, in turn, can contribute to muscular and functional alterations. Thus, the data enhance the importance of considering eating-related behaviors to be associated to the patient’s complaint.